The Influence of Social Media, Beauty Vlogger Reviews and Brand Image on Buying Interest in Wardah Cosmetic Products - Christinna Chen; Leonardo Chen; Willy Cahyadi; Rizki Wulanita Batubara (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth, with Wardah as one of the local brands that has managed to attract the attention of consumers, especially students, through the concept of halal and high quality. This study aims to analyze the influence of social media, beauty vlogger reviews, and brand image on the interest in buying Wardah cosmetic products among students in Tebing Tinggi. This research uses a survey-based quantitative approach, involving a sample size population using the cochran formula so that a sample of 96 respondents was selected by purposive sampling. Data was collected through questionnaires and analyses carried out, namely instrument test, validity test, reliability test, and classical assumption test. In the classical assumption test, the normality test, the multicollinearity test, the heteroscedasticity test were carried out and the multiple linear regression analysis test and the hypothesis test were carried out using the T & F test with SPSS software. The results of the study show that social media has a significant effect on buying interest, beauty vlogger reviews do not have a significant effect on buying interest, and brand image has a significant effect on buying interest. Simultaneously, these three variables contributed 48.4% to buying interest. These findings are expected to support the development of more effective digital marketing strategies in the cosmetics industry. Abstrak - Industri kosmetik di Indonesia mengalami pertumbuhan pesat, dengan wardah sebagai salah satu merek lokal yang berhasil menarik perhatian konsumen, khususnya mahasiswa, melalui konsep halal dan kualitas tinggi. Penelitian ini bertujuan untuk menganalisis pengaruh media sosial, review beauty vlogger, dan brand image terhadap minat beli produk kosmetik Wardah di kalangan mahasiswa di Tebing Tinggi. Peneltian ini menggunakan pendekatan kuantitatif berbasis survei, melibatkan populasi ukuran sampel menggunakan rumus cochran sehingga didapatkan jumlah sampel sebesar 96 responden yang dipilih secara purposive sampling. Data dikumpulkan melalui kuesioner dan analisis yang dilakukan yaitu uji instrumen, uji validitas, uji reliabilitas, uji asumsi klasik. Dalam uji asumsi klasik menggunakan uji normalitas, uji multikolinearitas, uji heteroskedastisitas lalu melakukan uji analisis regresi linier berganda dan uji hipotesis menggunakan uji T & uji F dengan software SPSS. Hasil penelitian menunjukkan bahwa media sosial berpengaruh signifikan terhadap minat beli, review beauty vlogger tidak berpengaruh signifikan terhadap minat beli, dan brand image berpengaruh signifikan terhadap minat beli. Secara simultan, ketiga variabel tersebut berkontribusi sebesar 48,4% terhadap minat beli. Temuan ini diharapkan dapat mendukung pengembangan strategi pemasaran digital yang lebih efektif di industri kosmetik.